Microglia-derived extracellular vesicles in homeostasis and demyelination/remyelination processes - Wies Mancini, Victoria Sofia Berenice (2023)
Microglia (MG) play a crucial role as the predominant myeloid cells in the central nervous system and are commonly activated in multiple sclerosis. They perform essential functions under normal conditions, such as actively surveying the surrounding parenchyma, facilitating synaptic remodeling, engulfing dead cells and debris, and protecting the brain against infectious pathogens and harmful self-proteins. Extracellular vesicles (EVs) are diverse structures enclosed by a lipid bilayer that originate from intracellular endocytic trafficking or the plasma membrane. They are released by cells into the extracellular space and can be found in various bodily fluids. EVs have recently emerged as a communication mechanism between cells, enabling the transfer of functional proteins, lipids, different RNA species, and even fragments of DNA from donor cells. MG act as both source and recipient of EVs. Consequently, MG-derived EVs are involved in regulating synapse development and maintaining homeostasis. These EVs also directly influence astrocytes, significantly increasing the release of inflammatory cytokines like IL-1β, IL-6, and TNF-α, resulting in a robust inflammatory response. Furthermore, EVs derived from inflammatory MG have been found to inhibit remyelination, whereas Evs produced by pro-regenerative MG effectively promote myelin repair. This review aims to provide an overview of the current understanding of MG-derived Evs, their impact on neighboring cells, and the cellular microenvironment in normal conditions and pathological states, specifically focusing on demyelination and remyelination processes.